A guide in installing large-scale PV power plant for self consumption mechanism - Senol, M.; Abbasoglu, S.; Kukrer, O.; Babatunde, A. A. (Pergamon-Elsevier Science Ltd, 2016)
The objective of this study is to optimize the design of a large scale photovoltaic power plant. A methodology is proposed to guide the investors and technical staff in the design of such a system, with core emphasis on self-consumption policy. A flowchart of the process, that uses site survey, system components, associated costs, meteorological data, load analysis, is created. The optimum capacity of a large-scale PV power plant is determined by an iterative approach as stated in the flowchart, which considers the payback period as the decision criterion. A case study is carried out in Cyprus International University (CIU) in order to support the proposed methodology. The dynamics of this study is unique, in that, the policy governing Renewable Energy Sources in Northern Cyprus does not allow the electricity authority to provide value for the electricity fed into the grid by self-consumption renewable energies. Simulations are performed by PV*SOL for different capacities varying from 450 to 1250 kW(p). Two different analyses have been conducted by considering the current and the predicted electricity demand of CIU. As a result, two optimum system sizes for current and predicted demands are obtained as 850 kW(p) and 1200 kW(p) respectively. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Solar energy; Large-scale PV power plant; Self-consumption; Northern Cyprus